Preservasi Warisan Budaya Dan Religi Makam Sunan Pandanaran Di Kecamatan Bayat Dalam Meningkatkan Ekonomi Lokal Melalui Sistem Creative Village - Adam Satria Buana; Anindya Hias Bestari; Aniworo Nuladani; Vanisa Anggreta Sari; Zulfa Navida; Anastasya Egidia Amanda; Lu’lu Nabila Khansa; Melta Meliano Putri; Prima Pashwa Alkahf; Sri Rum Giyarsih, M.Si. (JPG (Jurnal Pendidikan Geografi), 2023)
Abstract: Research conducted in the Area of the Complex of the Tomb of Sunan Pandanaran motivated because there is a potential of the economy and culture in the area of the Tomb of Sunan Pandanaran aims to determine and develop the design of planing the development of the potential of culture and religion in the Tomb of Sunan Pandanaran. Knowing that the system is creative village is able to improve the local economy by way of empowerment of the function of the people who live around the Tomb of Sunan Pandanaran. The method used in this research is descriptive qualitative method with primary data obtained from the history Book of Sunan Pandanaran and oral history in collecting research data and observations directly to the Tomb of Sunan Pandanaran. Meanwhile, the secondary data obtained from the plotting of the self with Google Street Map and for the design of the planning of the building using the application SketchUp. This research produces output in the form of planning the design of infrastructure on the economy and the addition of supporting health facilities. The results of the second form of the digitization of information in the form of ArcGis StoryMaps assembled using the Quick Response (QR) Code that is contained in the Tomb of Sunan Pandanaran as a condition of the fulfillment of the principle of creative village in order to improve the quality of existing infrastructure. The results of the third form of analysis of the potential of the cultural heritage and religious Sunan Pandanaran..  Keywords: Creative Village, Culture, Preservation, Religion Abstrak: Penelitian yang dilakukan di Kawasan Kompleks Makam Sunan Pandanaran dilatarbelakangi oleh adanya potensi ekonomi dan budaya di kawasan Makam Sunan Pandanaran. Penelitian ini bertujuan untuk mengetahui serta mengembangkan desain perencanaan pengembangan potensi budaya dan religi di Makam Sunan Pandanaran sekaligus mengetahui bahwa sistem creative village mampu meningkatkan ekonomi setempat dengan cara pemberdayaan fungsi masyarakat yang tinggal di sekitar Makam Sunan Pandanaran. Metode yang digunakan dalam penelitian ini adalah metode deskriptif kualitatif dengan data primer yang diperoleh dari Buku Babad Sunan Pandanaran dan oral history dalam mengumpulkan data penelitian, serta observasi langsung ke kawasan Makam Sunan Pandanaran. Sementara itu, data sekunder diperoleh dengan cara plotting mandiri dari Google Street Map untuk desain perencanaan bangunan yang kemudian diolah menggunakan software SketchUp. Penelitian ini menghasilkan output berupa perencanaan desain infrastruktur pada kawasan ekonomi dan penambahan fasilitas penunjang kesehatan. Penelitian ini juga menghasilkan digitalisasi informasi berupa ArcGis StoryMaps yang dirangkai menggunakan kode Quick Response (QR) Code yang terdapat di Makam Sunan Pandanaran sebagai syarat terpenuhinya prinsip creative village guna meningkatkan kualitas infrastruktur yang ada. Hasil ketiga berupa analisis potensi kawasan warisan budaya dan religi Sunan Pandanaran. Kata kunci: Budaya, Creative Village, Preservasi, Religi